Effect of Sacubitril-Valsartan on Restoration and Maintenance of Sinus Rhythm in Patients With Persistent Atrial Fibrillation - Chen, Qingsong; Chen, Yunlin; Qin, Fang; Du, Huaan; Gan, Chunxia; Zhou, Bei; Wang, Na; Xiao, Mingyang; Ou, Zhenhong; Zhao, Wei; Cui, Ben; Liu, Zengzhang; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Existing studies have shown that sacubitril-valsartan ameliorated atrial remodeling in atrial fibrillation (AF) and favored maintenance of sinus rhythm in patients with AF and heart failure. However, the effect of sacubitril-valsartan in patients with persistent AF is yet unknown. We aimed to evaluate the effect of sacubitril-valsartan on restoration and maintenance of sinus rhythm in patients with persistent AF who underwent electrical cardioversion (ECV). Method Consecutive patients with persistent AF who underwent ECV between 1 January 2016 and 30 September 2020 were investigated in this retrospective cohort study. All eligible patients were categorized into sacubitril-valsartan users and sacubitril-valsartan non-users based on whether they received treatment with sacubitril-valsartan or not. The endpoint was ineffictive ECV, defined as the composite of failure to terminate AF or any recurrence of AF during 30 days follow-up. Results A total of 76 patients were enrolled in this study, including 28 sacubitril-valsartan users and 48 non-users. Within a follow-up of 30 days after ECV, the endpoint had occurred in 7 (25%) of 28 sacubitril-valsartan users and 25 (52%) of 48 non-users. Significantly lower rate of ineffictive ECV in sacubitril-valsartan users compared with non-users was shown in Kaplan-Meier survival curves (P = 0.02; Log-rank test). Multivariate Cox regression analysis indicated that sacubitril-valsartan use (hazard ratio [HR], 0.35; 95% confidence interval [CI], 0.14–0.91), amiodarone use (HR, 0.32; 95% CI, 0.13–0.78), left atrial diameter ≤ 39 mm (HR, 0.21; 95% CI, 0.06–0.71) were independently associated with a decreased rate of ineffective electrical cardioversion. Conclusion Use of sacubitril-valsartan is associated with a significantly decreased risk of ineffective ECV compared with non-users in patients with persistent AF.